Healthcare settings: the best ways to mitigate errors - Camara, Mohamed Elmahady; Camara, Nafissatou; Camara, Ansoumane Yassima; Traore, Falaye (International Journal Of Community Medicine And Public Health, 2017)
Background: The aim of this article is to analyze the concept of medical errors and to find out the best ways to minimize them. This article produces some practical examples of situations of errors in medical settings. Also, it explains the contrast between developing countries and developed countries about reporting errors in the medical setting. Methods: This article is prospective and it is analytic. It is based on factual approaches obtained from articles and books. It is based on the statistics obtained from data about medical errors in the United States. It also addresses the situation of medical errors in Africa. Results: Medical errors are a real public health problem worldwide. Since there is a lack of medical error evaluation structures in some countries, the outcome is always catastrophic. In Africa; for example, many countries do not properly report the data. In the Republic of Guinea, there is no official data concerning medical errors. In those countries, there is no risk for physicians to lose their licenses because there are no structures to control their errors. While in the United States, medical errors are a big concern; the reporting systems of errors are developed. Errors in the United States can cause the physicians the suspension of their licenses and/or the process can result in their revocation. Medical errors happen everywhere in the world. In developed countries, even though the number of deaths due to errors is elevated; however, it is better addressed than it is in developing countries. In some countries, there is no appropriate data allowing to analyze and to address errors. In the United States, on who stayed in Liberia, went to the Texas Health Presbyterian Hospital for a fever. He informed the nurse about his travel history. Unfortunately, the patient (Dancan) was sent home after that initial visit. The hospital was criticized. It is possible to affirm that this was a big medical error. The patient died on October 08, 2014. Conclusion: Medical errors are a serious Public Health problem worldwide; especially in Africa. The healthcare system is not free from total risks. Because errors are inherent to human nature, blaming or immediately terminating an employee involved in an error is not the right approach. Punitive approach is not effective. Instead, training and educational approach are the best ways to handle adverse event based on the Just Culture concept. Just Culture; Electronic Medical Records; Patient and Family Involvement in the Care; and the Appropriate Medical Professional Training can help to mitigate errors in healthcare settings. Those approaches will help to analyze the root cause; which would allow us to determine the real cause of errors, and find out the ways to mitigate those errors from happening in the future.